The impact of IBD medications on risk of pneumonia and pneumonia‐related hospitalisation: a nationwide cohort study of 56 410 IBD patients. Issue 1 (19th October 2021) - Khan, Nabeel; Patel, Dhruvan; Trivedi, Chinmay; Pernes, Tyler; Kavani, Himanshu; Xie, Dawei; Yang, Yu‐Xiao
Summary: Background: There are limited data on the incidence of pneumonia and pneumonia‐related hospitalisation in the IBD population, and on any association of IBD medications with such outcomes. Aims: To evaluate the impact of IBD medications on the risk of pneumonia, pneumonia‐related hospitalisations and death. Methods: We conducted a retrospective cohort study of IBD patients from the nationwide Veteran Affairs (VA) dataset. The exposure of interest was different IBD medication groups. We estimated the incidence rate of pneumonia, pneumonia‐related hospitalisation and mortality based on IBD medication subgroups. We used a multivariable Cox regression to estimate the adjusted hazard ratios (AHR) and 95% confidence intervals (CIs) for these outcomes. Results: Out of 56 410 patients with IBD, 3759 developed pneumonia, 1489 were hospitalised, and 248 died within 30 days of their pneumonia diagnosis. The crude incidence rates of pneumonia, pneumonia‐related hospitalisation and pneumonia‐related mortality were 6.47, 2.52 and 0.43, respectively, per 1000 person‐years. In multivariable Cox regression analysis, compared to 5‐ASA alone, anti‐TNF medication was associated with an increased risk of pneumonia (AHR 1.39; 95% CI 1.22‐1.59) and hospitalisation (AHR 1.61; 95% CI 1.31‐1.98). Use of prednisone in the prior 30 days was associated with increased risk of pneumonia (AHR 2.14; 95% CI 1.92‐2.38) and hospitalisation (AHR 2.44; 95% CI 2.08‐2.88). Conclusion: Anti‐TNF medications and prednisone use may be associated with increased risk of developing pneumonia and pneumonia‐related hospitalisation. Physicians should evaluate the risk–benefit ratio of IBD medications, especially in the elderly population.